ANALISIS KEBUTUHAN AIR BERSIH DI WILAYAH KECAMATAN KUTA DAN KUTA SELATAN KABUPATEN BADUNG - I MADE SATYA GRAHA; ANAK AGUNG RATU RITAKA WANGSA (Universitas Mahasaraswati K. Mataram, 2023)
Water as the basis of life is very important for human life. Population growth is increasing the need for potable water in communities, especially in southern Badung County. The source of drinking water demand is managed by PDAM Tirta Mangutama Badung Regency. The problem is that in the two districts, all the communities that are not part of the PDAM do not have drinking water. Considering this, it is necessary to identify the needs of people who need water in the community, to have clean water and sanitation facilities for houses and hotels in Kuta and South Kuta in the next five years. of the lake estuary IPA. This study was conducted by evaluating the water treatment process to obtain clean water, analyzing the clean water requirements and analyzing the operating costs for the treatment of clean water. The analysis shows that household and hotel water needs will increase by ±10% by 2025. The clean water capacity of the Estuary DAM IPA is 500 liters/second, which is still sufficient for the needs drinking water for homes and hotels in Kuta. South Kuta District. Water treatment operating cost requirements (chemical costs and power plant costs) increased by ±7% by 2025